2013
DOI: 10.1128/mbio.00366-13
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio cholerae ToxR Downregulates Virulence Factor Production in Response to Cyclo(Phe-Pro)

Abstract: Vibrio cholerae is an aquatic organism that causes the severe acute diarrheal disease cholera. The ability of V. cholerae to cause disease is dependent upon the production of two critical virulence determinants, cholera toxin (CT) and the toxin-coregulated pilus (TCP). The expression of the genes that encode for CT and TCP production is under the control of a hierarchical regulatory system called the ToxR regulon, which functions to activate virulence gene expression in response to in vivo stimuli. Cyclic dipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
85
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(94 citation statements)
references
References 53 publications
7
85
2
Order By: Relevance
“…This observation is in apparent contradiction to our finding that when cpxR is overexpressed in V. cholerae El Tor strain C6706, it upregulates the expression of the virulence regulator ToxR (54), an activator of ctxA and tcpA expression (16,56). In this regard, a recent study showed for the first time that ToxR can negatively regulate the production of CT and TCP in response to cyclic dipeptides (CDPs) (89). Bacterial production of cyclo(Phe-Pro) leads to ToxR-mediated activation of the LysR transcription factor LeuO, which in turn represses CT production (89).…”
Section: Figcontrasting
confidence: 55%
See 1 more Smart Citation
“…This observation is in apparent contradiction to our finding that when cpxR is overexpressed in V. cholerae El Tor strain C6706, it upregulates the expression of the virulence regulator ToxR (54), an activator of ctxA and tcpA expression (16,56). In this regard, a recent study showed for the first time that ToxR can negatively regulate the production of CT and TCP in response to cyclic dipeptides (CDPs) (89). Bacterial production of cyclo(Phe-Pro) leads to ToxR-mediated activation of the LysR transcription factor LeuO, which in turn represses CT production (89).…”
Section: Figcontrasting
confidence: 55%
“…In this regard, a recent study showed for the first time that ToxR can negatively regulate the production of CT and TCP in response to cyclic dipeptides (CDPs) (89). Bacterial production of cyclo(Phe-Pro) leads to ToxR-mediated activation of the LysR transcription factor LeuO, which in turn represses CT production (89). At this point, we cannot say whether Cpx-mediated activation of ToxR production is involved in the inhibition of CT and TCP via CDPs or some other mechanism (Fig.…”
Section: Figmentioning
confidence: 99%
“…The resulting analysis showed that cVV exhibited an IC 50 of~166 mM, which confirmed that cVV exhibited more potent antivirulence activity relative to cFP, which exhibited an IC 50 of~300 mM (Bina & Bina, 2010;Bina et al, 2013).…”
Section: Results Cvv Is a Concentration-dependent Inhibitor Of Ct Promentioning
confidence: 51%
“…We therefore cultured the respective mutants (Dlrp : : Cm, DvpsR, DtoxRS and DleuO) and JB58 under AKI conditions in the presence and absence of 0.5 mM cVV and quantified aphA expression by qRT-PCR. The toxRS mutant was included to test whether cVV activity was dependent on ToxR as was observed with cFP (Bina et al, 2013). The results showed that cVV exhibited inhibitory activity in the lrp, vpsR and leuO deletion backgrounds, as indicated by the cVV-dependent inhibition of aphA expression in each strain (Fig.…”
Section: Cvv Signals Through the Toxr Virulence Regulonmentioning
confidence: 99%
See 1 more Smart Citation